2002
DOI: 10.1073/pnas.192449699
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of genomic evolution caused by enhanced mutation rate in endocellular symbionts

Abstract: Endosymbionts, which are widely observed in nature, have undergone reductive genome evolution because of their long-term intracellular lifestyle. Here we compared the complete genome sequences of two different endosymbionts, Buchnera and a protist mitochondrion, with their close relatives to study the evolutionary rates of functional genes in endosymbionts. The results indicate that the rate of amino acid substitution is two times higher in symbionts than in their relatives. This rate increase was observed uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
110
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(121 citation statements)
references
References 56 publications
(62 reference statements)
10
110
1
Order By: Relevance
“…Conversely, although the most extensively sampled environment in DNA surveys is clearly the oceanic euphotic zone (Epstein and López-García 2008), we did not find any sequence related to LKM11 in published molecular surveys from this environment, suggesting that their potential chytrid and oomycete hosts may be rare or even absent in surface marine waters. Furthermore, the frequent presence of long branches inside the ''Rozellida'' agrees with the hypothesis that this group might be composed to a large extent (if not entirely) of parasites, as parasites, in particular intracellular ones, very often have accelerated evolutionary rates (Itoh et al 2002).…”
Section: Resultssupporting
confidence: 80%
“…Conversely, although the most extensively sampled environment in DNA surveys is clearly the oceanic euphotic zone (Epstein and López-García 2008), we did not find any sequence related to LKM11 in published molecular surveys from this environment, suggesting that their potential chytrid and oomycete hosts may be rare or even absent in surface marine waters. Furthermore, the frequent presence of long branches inside the ''Rozellida'' agrees with the hypothesis that this group might be composed to a large extent (if not entirely) of parasites, as parasites, in particular intracellular ones, very often have accelerated evolutionary rates (Itoh et al 2002).…”
Section: Resultssupporting
confidence: 80%
“…selection pressure, and adaptive evolution in the laboratory lineage, can lead to elevated evolutionary rates (34,35). The first two reasons, i.e., increased mutation rate and more generations, cannot be the major underlying reasons because the evolutionary rate difference observed above for amino acid change was normalized by synonymous change.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, animal mitochondrial DNA evolves much more rapidly (42)(43)(44) than plant mitochondrial and chloroplast genes (45,46). It has been suggested that the acceleration of molecular evolution in the small genome of endosymbiotic bacteria, Buchnera, is mainly because of enhanced mutation rate (47). It was shown that the E. coli RecA protein functions in the chloroplast of the green algae Chlamydomonas to regulate recombination in a way similar to that in E. coli (48).…”
Section: Acquisition Of Reca Genes By Eukaryotic Nuclear Genomes By Mmentioning
confidence: 99%